Skaneņa R mācīšana 5-6 gadus veciem bērniem ar skaņu izrunas traucējumiem - Reimane, Liene (Latvijas Universitāte, 2021)
Diplomdarba mērķis: Teorētiski izzināt korekcijas iespējas skaneņa R mācīšanai un praktiski izmantot dažādus mācību paņēmienus skaneņa R izrunas traucējumu mazināšanā. Teorētiski tiek izzināta un analizēta 5— 6 gadus vecu bērnu fiziskā, kognitīvā, sociālā un emocionālā attīstība, kā arī bērnu attīstības īpatnības valodas un runas traucējumu gadījumā. Tiek raksturots skanenis R no fonētiskā un logopēdiskā skatījuma, analizēta tā pareiza izruna un izrunas traucējumu veidi. Praktiski tiek veikta bērnu attīstības un runas izpēte. Raksturota bērnu individuālā skaņas izrunas attīstība, izmantojot dažādus mācību paņēmienus skaneņa R mācīšanā. Tiek analizēti iegūtie dati pētījumā. Diplomdarba saturs: 1.5— 6 gadīgu bērnu vecumposma raksturojums; 2.skanenis R un tā mācīšana; 3.pētījums par skaneņa R mācīšanu 5— 6 gadus veciem bērniem ar skaņu izrunas traucējumiem. Diplomdarbu var izmantot: pedagoģijas un logopēdijas studenti, skolotāji logopēdi, vecāki.

The aim of the paper: To cognize theoretical opportunities of voiced consonant R teaching, and to use practically various teaching techniques for voiced consonant R pronunciation disorders reducing. The physical, cognitive, social and emotional development of 5— 6 years old children is explored and analyzed theoretically. Also are explored and analyzed the peculiarities of children’s development in case of language and speech disorders. The voiced consonant R is described form the phonetic and speec therapy point of view, also correct pronunciation and pronunciation disordes of the voiced consonant R is analyzed. The research of children’s development and speech development are examined practically. Children’s individual development of sound pronunciation, using different techniques of teaching voiced consonant R, is described as well. The study results are analyzed. The content of paper: 1.Characteristics of 5— 6 years old children; 2.Voiced consonant R and teaching of it; 3.Study about the voiced consonant R teaching of 5— 6 years old children with sound pronunciation disorders. Diploma paper can be used: pedagogy and speech therapy stundents, speech therapist, parents.
Voiced consonant R teaching of 5-6 years old children with sounds pronunciation disorders
Keywords: Pedagoģija; skanenis R; skaņu izrunas traucējumi; 5— 6 gadus veci bērni; artikulācijas aparāta vingrinājumi